REGIONAL BANKS OF RUSSIA: PROBLEMS OF GROWTH AND DEVELOPMENT PROSPECTS - N. S. Voronova; O. S. Miroshnichenko (Финансы: теория и практика, 2017)
By the spatial location of credit institutions, the banking system of Russia includes two large groups of banks: regional banks and banks registered in Moscow and the Moscow Region. The activities of banks of the two groups are characterized by certain specifics. In view of the above, the purpose of this study was to identify, systematize and critically evaluate the current trends in the development of regional banks in Russia. The methods used include analysis and synthesis, induction and deduction, comparison, system analysis, selective observation. The analysis of official data of the Russian Central Bank for 2007–2016 showed that the trends of active credit institutions to shrink in number are common to both regional and Moscow credit organizations. The profits received by regional banks are incommensurably small compared to the profits of Moscow-based banks but are subject to much less volatility. The gap between amounts of ruble loans provided by credit institutions of the two groups under analysis is dramatically widening: to non-financial organizations in 2007–2016 and to individuals since 2011. After 2012, the amount of ruble loans extended to non-financial organizations by regional banks stabilized at about 2000 RUR billion, while the corresponding indicator for credit institutions in the capital region slowed down its growth in 2015–2016. Starting with 2009, the gap between investments in debt securities made by regional banks and credit institutions of Moscow and the Moscow Region has sharply widened; such bank investments in the capital region are noted to be highly volatile. Credit institutions of the Volga and North-Western federal districts dominate in the field of debt securities investment. Regional banks are running the conventional banking business primarily by lending and placing limited funds in securities of third-party issuers. The indicators of regional banks differ significantly by federal districts.